ANALISIS PENYELUNDUPAN PAJAK KEPABEANAN ATAS IMPORTASI MERCHANDISE K-POP PADA KOMUNITAS AUTOBASE X TWITTER - Alkaina Salsabila; Ahmad Zakie Mubarrok (Jurnal Riset Akuntansi Politala, 2024)
This study aims to analyze and identify the mode operation of tax smuggling practices by business actors of K-Pop merchandise entrustment services through their shipment of goods. Customs officers must inspect every shipment of goods entering the country to ensure the legality of the goods and to find out the tax obligations. The importation of K-Pop merchandise commodities from the South Korean creative industry into Indonesia was carried out to fulfill the demand of South Korean culture fans. This study uses a descriptive qualitative method with a case study approach. Data collection and analysis were obtained through triangulation of interview techniques, observation, and documentation of sources. The results of this study show that there is tax smuggling in the K-Pop merchandise purchase service business through consignments. Importers often practice the manipulation of customs administrative documents to minimize the amount of import duty bills and tax burdens on their shipment goods. Through changes in the customs value of consignment goods in the consignment note notification document with those in the actual purchase transaction document, they are causing differences in the application of customs documents and the calculation rate of Import Duty and Tax in the Framework of Import (PDRI) that must be paid to the state.